Psalms - Brueggemann, Walter, 1933- (New Cambridge Bible commentary, 2014)
"This text introduces the book of Psalms and provides an exposition of each psalm with attention to genre, liturgical connections, societal issues, and the psalm,♯s̥ place in the book of Psalms as a whole. The treatments of the psalms feature a close look at particular issues raised by the text and the encounters between the world of the psalm and the world of contemporary readers. The exposition of each psalm provides a reader,♯s̥ guide to the text in conversation with relevant theological issues"--